2016
DOI: 10.4314/ejhs.v26i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Premarital sex in the last twelve months and its predictors among students of Wollega University, Ethiopia

Abstract: BACKGROUND: Premarital sex increases the risk of unintended pregnancy and sexually transmitted infections including HIV if unprotected and contraception is not used. Thus, the objective of this study was to assess premarital sex in the last twelve months and its predictors among regular undergraduate students of Wollega University. METHODS: A cross-sectional survey using pretested, structured questionnaire was conducted on a total of 704 regular undergraduate students of Wollega University from February to Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
23
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 20 publications
10
23
3
Order By: Relevance
“…In Ethiopia sex before marriage and early initiation of sex is still high among adolescents and as a consequence they are becoming a victim of different negative outcomes of the practice (7), (8,12). Different articles indicated that age, gender, residence, educational level, watching pornography, Khat and alcohol utilization had been contributing for sex before marriage, but they are not consistent, still there is controversy among different reports (1), (3), so it is mandatory to identify the prevalence and associated factors of premarital sexual practice in the specified study area that can give information for Health policy makers, local health program managers and other responsible bodies that focus on health related issues.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia sex before marriage and early initiation of sex is still high among adolescents and as a consequence they are becoming a victim of different negative outcomes of the practice (7), (8,12). Different articles indicated that age, gender, residence, educational level, watching pornography, Khat and alcohol utilization had been contributing for sex before marriage, but they are not consistent, still there is controversy among different reports (1), (3), so it is mandatory to identify the prevalence and associated factors of premarital sexual practice in the specified study area that can give information for Health policy makers, local health program managers and other responsible bodies that focus on health related issues.…”
Section: Introductionmentioning
confidence: 99%
“…Of the included articles, 41.6% of the included studies were conducted from Oromia region [5,11,18,24,29,33,35,[37][38][39]: seven studies from Amhara region [19-22, 28, 30, 34]: four studies were reported from SNNPR [9,26,27,32]: two articles in Tigray [23,25] and one articles [31] conducted in Addis Ababa city administration. Except one study which was conducted at community level in Tigray region [23], all other studies were done at the institutional level.…”
Section: Resultsmentioning
confidence: 99%
“…Once more, similar with the reports from Asian countries and Nepal [10,54], Youths who drink alcohol were more likely get involved in premarital sexual practice than those who didn't drink alcohol. This can be possibly explained by that risky sexual behavior such as smoking and alcohol drinking is associated with higher approval of premarital sexual practice [5,6,17].…”
Section: Associated Factors Of Premarital Sexual Practices In Ethiopiamentioning
confidence: 99%
See 2 more Smart Citations